2003
DOI: 10.1016/s0020-7489(02)00043-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric nurses’ views on criteria for psychiatric intensive care: acute and intensive care staff compared

Abstract: Aim: To explore and investigate differences between the views of qualified nurses working in psychiatric intensive care units (PICUs) and acute care wards on which patients are appropriate for PICU care.Background: Previous research on the area of psychiatric intensive care highlights the great differences that exist in all aspects of service provision, from unit size and staffing levels to treatment approaches and physical environment. One of the most common areas of controversy is the type of client behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…In the fight against turbulence, the results make clear that strategies were questioned due to ethical considerations. Consistent with this, Bowers et al (2003) conclude that the least restrictive interventions should be pursued; Hall (2004) presents seclusion as a last resort. Morales and Duphorne (1995) advocate the use of less restrictive methods such as verbal interaction, medication as required, limit-setting, and use of quiet time.…”
Section: Caring Ethos In the Culture Of Stabilitymentioning
confidence: 66%
“…In the fight against turbulence, the results make clear that strategies were questioned due to ethical considerations. Consistent with this, Bowers et al (2003) conclude that the least restrictive interventions should be pursued; Hall (2004) presents seclusion as a last resort. Morales and Duphorne (1995) advocate the use of less restrictive methods such as verbal interaction, medication as required, limit-setting, and use of quiet time.…”
Section: Caring Ethos In the Culture Of Stabilitymentioning
confidence: 66%
“…At the same time, the increasing practice of keeping acute psychiatric wards locked is likely to have led to reduced transfers of patients to PICUs in order to prevent risk resulting from the patient absconding. 11,12 Finally, some new psychiatric units have opened that have no PICU provision at all, or, in other instances, PICU provision has been limited to a single site within a much larger multihospital NHS trust. The consequences and efficacy of these differing systems for managing high-risk patients has been neither compared nor evaluated on a wide scale.…”
Section: Psychiatric Intensive Care Unitsmentioning
confidence: 99%
“…violence, drugs and alcohol, Loubser et al 2009; staff opinions on admissions, Bowers et al 2003). Despite this, and the fact that PICUs are a more challenging environment, this does not appear to have compromised the quality of care that PICUs provide according to the methodology adopted.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Nurses working on acute wards are more likely to attribute problems, including violence, to drug and alcohol use than their PICU colleagues (Loubser et al 2009). Bowers et al (2003) studied the differences in the perspectives of acute and PICU nursing staff in relation to appropriate admissions for a PICU. They found that acute nursing staff took into account a smaller range of risk factors when considering admission and had a lower threshold for suitability when compared to PICU staff.…”
Section: Introductionmentioning
confidence: 99%